2016
DOI: 10.1007/s11255-016-1470-1
|View full text |Cite
|
Sign up to set email alerts
|

Modified laparoscopic simple enucleation with single-layer suture technique versus standard laparoscopic partial nephrectomy for treating localized renal cell carcinoma

Abstract: MLSE may confer shorter warm ischemic time, almost no need for tumor bed suturing and less grade III complications than SLPN, with similar oncologic outcomes. MLSE may be safe and acceptable for patients undergoing partial nephrectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 29 publications
2
36
0
Order By: Relevance
“…In the study, mean operative time and warm ischemia time were 104.3±18.2 min and 21.3±3.5 min, respectively. The results are comparable to previous studies ( 11 , 12 ). SE is possible because most localized renal masses are enveloped by a peritumoral pseudocapsule containing muscle, reticulin and collagens ( 6 ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In the study, mean operative time and warm ischemia time were 104.3±18.2 min and 21.3±3.5 min, respectively. The results are comparable to previous studies ( 11 , 12 ). SE is possible because most localized renal masses are enveloped by a peritumoral pseudocapsule containing muscle, reticulin and collagens ( 6 ).…”
Section: Discussionsupporting
confidence: 91%
“…NSS includes sharp excision, namely partial nephrectomy (PN) and blunt dissection, namely simple enucleation (SE). Given the advantages that SE had comparable oncological outcomes with PN and less complications than PN, SE was recommended to treat localized renal tumors ( 9 12 ). Even for some highly complex renal tumors, Serni S, et al ( 8 ) reported that SE was an effective treatment with a potential key role to widen the NSS indications according to guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, Lu et al. compared 280 simple enucleations using a single‐layer technique with105 standard LPNs using a double‐layer suture. Even with more lesions with a PADUA score >10, (22.2% vs 11.4%; P = 0.017), the simple enucleation group achieved lower WIT and a lower complication rate, with similar oncological outcomes.…”
Section: Resultsmentioning
confidence: 99%